Classical Odia in historical perspective : the document submitted for classical status of Odia language by Culture Department, Govt. of Odisha to Ministry of Culture, Govt. of India - Pattanayak, Debi Prasanna; Pattanayak, Debi Prasanna; Prusty, Subrat Kumar; Prusty, Subrat Kumar (Odisha Sahitya Akademi, 2015)
On Oriya language naturalization; document submitted for official sanction as one of the classical Indian languages